READING COMPREHENSION TOWARDS QAR STRATEGIES AT SMPN 4 PEMATANGSIANTAR - Sianipar, Cindy Sylvia; Sibuea, Devi Winanda (Transpublika Publisher, 2022)
This study aims to (1) determine the significant difference in reading comprehension skills between students who were taught using the QAR strategy and students who were taught without using the QAR strategy in class VIII SMP Negeri 4 Pematangsiantar. This research is a quantitative research with a quasi-experimental research method. The research design was a pretest and posttest control group design. The data analysis technique used was t-test with a significance level of 5%. T-test analysis of posttest data of the experimental group and the control group, obtained th of 3.523 and p of 0.001 (p <0.05). The results of the t-test analysis of the experimental group's pretest and posttest data obtained th 12,919 and p of 0.000 or (p <0.05). The average gain score for the experimental group was 5.41 and the control group average was 2.78. Based on these data, the conclusions of this research are (1) there is a significant difference in reading comprehension ability between students who are taught using the QAR strategy and those taught without using the QAR strategy in class VIII SMP Negeri 2 Tempel, (2) the QAR strategy is effectively used in learning reading comprehension in grade VIII SMP Negeri 4 Pematangsiantar.